(untitled) (Research, Society and Development, 2022)
The aim of this study was to compare the antimicrobial activity of the essential oil (EO) of cinnamon (Cinnamomum verum) and its major compound cinnamaldehyde against Staphylococcus aureus (ATCC 14458) and bacteria isolated from mastitic milk. Cinnamon EO was chemically characterized by gas chromatography/mass spectrometry (GC-MS). The Minimum Inhibitory Concentration (MIC) and the Minimum Bactericidal Concentration (MBC) of cinnamon EO and cinnamaldehyde were determined, as well as the effects of MIC and CBM on S. aureus cells, visualized by Scanning Electron Microscopy (SEM) and Microscopy Transmission Electronics (TEM). A synergistic evaluation of the EO of cinnamon and cinnamaldehyde with conventional antimicrobials was also performed. Results: The substance cis-cinnamaldehyde (58.7%) was identified as the major component of cinnamon EO. The MIC values determined against all tested strains ranged between 0.8 and 1.6 mg.mL-1. SEM and TEM images (post-treatment with cinnamon EO and cinnamaldehyde) showed coarse-shaped S. aureus cells with residues adhered to the cell wall and irregular and irregular regions at the points of cell division. Conclusion: Both cinnamon EO and cinnamaldehyde showed undetermined antimicrobial activity combined with conventional antimicrobials, which brings the prospect of their ability to intensify the antimicrobial action of veterinary drugs used in the treatment of mastitis caused by multidrug-resistant bacteria.